Immune recognition of somatic mutations leading to complete durable regression in metastatic breast cancer. (June 2018) - Zacharakis, Nikolaos; Chinnasamy, Harshini; Black, Mary; Xu, Hui; Lu, Yong-Chen; Zheng, Zhili; Pasetto, Anna; Langhan, Michelle; Shelton, Thomas; Prickett, Todd; Gartner, Jared; Jia, Li; et al.
Abstract Immunotherapy using either checkpoint blockade or the adoptive transfer of antitumor lymphocytes has shown effectiveness in treating cancers with high levels of somatic mutations—such as melanoma, smoking-induced lung cancers and bladder cancer—with little effect in other common epithelial cancers that have lower mutation rates, such as those arising in the gastrointestinal tract, breast and ovary1–7 . Adoptive transfer of autologous lymphocytes that specifically target proteins encoded by somatically mutated genes has mediated substantial objective clinical regressions in patients with metastatic bile duct, colon and cervical cancers8–11 . We present a patient with chemorefractory hormone receptor (HR)-positive metastatic breast cancer who was treated with tumor-infiltrating lymphocytes (TILs) reactive against mutant versions of four proteins—SLC3A2, KIAA0368, CADPS2 and CTSB. Adoptive transfer of these mutant-protein-specific TILs in conjunction with interleukin (IL)-2 and checkpoint blockade mediated the complete durable regression of metastatic breast cancer, which is now ongoing for >22 months, and it represents a new immunotherapy approach for the treatment of these patients. Adoptive T cell therapy induced complete and durable remission in a patient with refractory metastatic breast cancer, providing proof of principle for this approach in breast cancer therapy.